A new species of Neocorynura from Ecuador (Hymenoptera: Halictidae), with notes on taxonomy of the genus - Smith-Pardo, Allan H. (Zootaxa, 2005)
A new species of the Neotropical bee genus Neocorynura (Halictinae: Augochlorini) is described and figured. Neocorynura miae, new species, combines characters traditionally used to distinguish Neocorynura from its relative Andinaugochlora (sensu Michener, 2000). The taxonomic placement of N. miae in the genus is presented and a revised diagnosis of Neocorynura is provided.